2019
DOI: 10.3390/soc9010026
|View full text |Cite
|
Sign up to set email alerts
|

Could 79 People Solarize the U.S. Electric Grid?

Abstract: Although wealth inequality has many established negatives, this study investigates a potential positive, unprecedented wealth concentration makes it possible for solutions to large and seemingly intractable problems to be deployed by convincing a relatively small number of individuals to invest. In order to probe this potential outcome of inequality, this study quantifies the number of people necessary to radically reduce the greenhouse gas emissions responsible for global climate destabilization from the U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…Finally, this study has shown that the rhetoric describing the transition to renewable energy as a high cost, such as the Wood Mackenzie analysis claiming the cost of shifting the U.S. power grid to 100 percent renewable energy would be $4.5 trillion [106], is misleading. Previous work has shown the wealthy could profit from large-scale PV deployment in the U.S. [107], and yet referring to the cost of a transition to renewable energy [108] remains the primary means of discourse. Some authors have pointed out that with the reduction in renewable energy technology prices such a conversion could be done with no costs [109] or even for less than it saves [110].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study has shown that the rhetoric describing the transition to renewable energy as a high cost, such as the Wood Mackenzie analysis claiming the cost of shifting the U.S. power grid to 100 percent renewable energy would be $4.5 trillion [106], is misleading. Previous work has shown the wealthy could profit from large-scale PV deployment in the U.S. [107], and yet referring to the cost of a transition to renewable energy [108] remains the primary means of discourse. Some authors have pointed out that with the reduction in renewable energy technology prices such a conversion could be done with no costs [109] or even for less than it saves [110].…”
Section: Discussionmentioning
confidence: 99%